Drivers of maritime green supply chain management - Muhamad Fairuz, Ahmad Jasmi; Fernando, Yudi (Elsevier Ltd, 2018)
The aim of this paper is to investigate the relationship between drivers of green maritime supply chain management and dimensions of maritime green supply chain management (MGSCM) practices. The theoretical model was developed from institutional theory to explore the drivers of MGSCM based on the Malaysian maritime sector. The online survey was used to collect the data. The sample was unit businesses that are involved in the green maritime supply chain. From 144 usable questionnaires, the findings found that green initiative, regulation and securities had partially significant relationships with the five dimensions of MGSCM. This study contributes to maritime transport literature by filling a gap with respect to survey-based research evidence of a theoretical model of MGSCM.